Perkawinan Beda agama antara "Illat dan Maqasid al-Syariah - Najib, Afifun Najib; siah khosiyah (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
This study examines the concept of interfaith marriage from the perspective of Islamic family law philosophy with the approach of ‘illat and Maqashid al-Syariah. This study is a normative-explanatory study, namely studying, explaining, and explaining descriptively qualitatively with a philosophical and conceptual approach. Data were obtained through literature studies. The analysis was carried out by studying the ‘illat or causes behind the law of interfaith marriage, as well as considering the main objectives of Islamic law or Maqashid al-Syariah. The research findings show that interfaith marriage in Islam can be viewed from the perspective of ‘illat (causal factor) and Maqashid al-Syariah (objectives of Islamic law). Based on ‘illat, interfaith marriage in Islam is considered an act that has the potential to cause mafsadat and disrupt the stability and integrity of the family and society. Meanwhile, according to Maqashid al-Syariah, interfaith marriage has two different perspectives: the first concerns the existence of interfaith marriage itself and the second concerns social mafsadat and its benefits for society. In conclusion, interfaith marriage can be considered from the perspective of Islamic family law philosophy with the approach of ‘illat and Maqashid al-Syariah. However, serious policies are still needed regarding the controversies and obstacles related to the practice of interfaith marriage in society.